2019
DOI: 10.1186/s12885-019-5550-3
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor heterogeneity index of breast carcinomas based on DNA methylation profiles

Abstract: Background Cancer cells evolve and constitute heterogeneous populations that fluctuate in space and time and are subjected to selection generating intratumor heterogeneity. This phenomenon is determined by the acquisition of genetic/epigenetic alterations and their selection over time which has clinical implications on drug resistance. Methods DNA extracted from different tumor cell populations (breast carcinomas, cancer cell lines and cellular clones) were analyzed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…Previous studies have categorized and quantified the heterogeneity of physiological features of spermatozoa to understand sperm subpopulation structures and their possible relationships with fertilizing ability . The heterogeneity of spermatozoa traits including shape, size, and head morphometrics, as well as chromatin and DNA methylation, has been linked to sperm function and fertilization rates. , In addition, heterogeneity has been widely used in assessing tumor states and prognostic treatment, indicating that heterogeneity is a basic property of the biological system and has good implications for evaluating individual states. Here, the associations between the heterogeneous features of exogenous metals and semen quality were robustly consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have categorized and quantified the heterogeneity of physiological features of spermatozoa to understand sperm subpopulation structures and their possible relationships with fertilizing ability . The heterogeneity of spermatozoa traits including shape, size, and head morphometrics, as well as chromatin and DNA methylation, has been linked to sperm function and fertilization rates. , In addition, heterogeneity has been widely used in assessing tumor states and prognostic treatment, indicating that heterogeneity is a basic property of the biological system and has good implications for evaluating individual states. Here, the associations between the heterogeneous features of exogenous metals and semen quality were robustly consistent.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments, we found that many compounds significantly inhibited the average cell motility but not the fast-moving cells, especially for the MDA-MB-231 cell line, which is known to be highly aggressive and heterogeneous. [80][81][82] The inability to stop those fast-moving cells might be explained by cancer cellular heterogeneity and the existence of redundant pathways. In our prior work, we have performed scRNA-Seq for highly migratory breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, e‐ITH, due to their dynamism and reversibility, evolve during a tumorigenic process in parallel to the acquisition of genomic alterations 99 . Specifically, in breast cancer it was reported that tumor subtype's behavior differ in terms of epigenetic heterogeneity, which could contribute to understand the different prognosis of these groups 100 …”
Section: Discussionmentioning
confidence: 99%